Kinship care and the Care Review. Issue 7 (2nd July 2022) - Harris, Alexandra Conroy
Abstract : Alexandra Conroy Harris, legal consultant at CoramBAAF, explains how proposals in the Care Review to encourage more children to be placed in kinship care arrangements could have unintended consequences